Implikasi Hukum Adanya Globalisasi Bisnis Franchise - Camelia Malik (Jurnal Hukum IUS QUIA IUSTUM, 2007)
This article aimed to study the Legal Implication Toward Globalization of Franchise Business. This study is important considered that there is no substantive law to regulate franchise business, particularly in Indonesia. By using quantitative analysis and legal approach, this study demontrated: First, globalization of franchise business causing globalization of law relating to the franchise agreement. It happens because when franchisor open a new franchise in one country, they not only  bring their business system, but also legal system to regulate their franchise agreement. Second, needs substantive law to regulate franchise in Indonesia in order to give legal protection for franchisee.